The Implications of Parental Consanguinity on the Care of Neonates. (August 2016) - Ng, Diana
Abstract : Background: Approximately 6% of births worldwide, 7.9 million children, are born with a serious genetic congenital abnormality each year. A factor thought to increase the prevalence of birth defects is parental consanguinity, which is a social custom practiced in at least 20% of the world's population. Purpose: The purpose of this article is to explore the relationship between consanguinity and congenital defects. This article also aims to enhance neonatal healthcare practitioners' comprehension of its implications for practice and research. Methods: A review of literature was compiled from a search of the online databases Cumulative Index of Nursing and Allied Health (CINAHL), PubMed, EBSCO MegaFILE, and Google Scholar. Results: Literature pertinent to this topic primarily consists of research studies that examine the inbreeding depression phenomenon through comparison of the prevalence of birth defects among the offspring of consanguineous and nonconsanguineous couples. Current studies indicate that the progeny of consanguineous couples are at an increased risk of congenital defects compared with those of nonconsanguineous couples. Implications for Practice: Consanguinity is one risk factor among many that can lead to a major birth defect. Relationships between consanguineous populations and neonatal healthcare practitioners such as registered nurses, advanced practice nurses, and physicians could significantly alter neonatal health outcomes. Specific recommendations such as genetic counseling and therapeutic communication are discussed. Implications for Research: Further studies need to investigate the connection between consanguinity and birth defects while controlling for nongenetic variables. Moreover, a focus on consanguineous communities in the United States would prove beneficial.